Association between Serum Vitamin D and Diabetic Retinopathy in Portuguese Patients with Type 1 Diabetes - Lopes, Miguel (2020)
Introduction: Recently, vitamin D has gained importance as a diabetes risk modifier. Our aim was to assess the association between serum vitamin D levels and the prevalence of diabetic retinopathy in patients with type 1 diabetes.Material and Methods: Retrospective review of a population of patients with type 1 diabetes followed in a Portuguese tertiary center. Patients were included if they had an ophthalmological evaluation and a serum 25-hydroxyvitamin D level determination within the same year. Logistic regression analysis was used to adjust for possible confounders.Results: We included 182 patients (47% male), and 57% (n = 103) had signs of diabetic retinopathy. We found a significant association between lower circulating levels of 25-hydroxyvitamin D levels and a greater prevalence of diabetic retinopathy after adjusting for confounders (duration of diabetes, estimated glomerular filtration rate, age, sex, metabolic control, season, dyslipidemia and hypertension) (OR = 0.94; 95% CI 0.90 - 0.99, p = 0.023). Longer duration of diabetes and worse metabolic control also remained associated with diabetic retinopathy in the multivariate analysis (OR = 1.20; 95% CI 1.13 - 1.27, p < 0.001 and OR = 4.13; 95% CI 1.34 - 12.7, p = 0.013, respectively).Conclusion: Lower levels of vitamin D were associated with an increased prevalence of diabetic retinopathy in patients with type 1 diabetes, after adjusting for possible confounders. Future controlled studies may elucidate the molecular routes for this association as well as the role of supplementation in the prevention of diabetes microvascular complications.